COMPARATIVE ANALYSIS OF SUSTAINABLE INDUSTRIAL DEVELOPMENT STRATEGIES IN WEST AFRICA AND SOUTHEAST ASIA: PATHWAYS TO PROSPERITY - Tidiane Guindo; Hak, Muhamad Bai'ul; Pahrudin, Pahrudin (Elastisitas : Jurnal Ekonomi Pembangunan, 2023)
The comparative analysis of industrial development strategies in West African and Southeast Asian nations, uncovered valuable insights for policymakers and researchers. The research has used a systematic literature review as its methodology. The study revealed common policy objectives, implementation approaches, and sectoral focuses shared by both regions, alongside the resulting outcomes. The lessons learned from successful industrialization experiences emphasized the significance of long-term vision, human capital investment, infrastructure development, regional integration, sustainable practices, and access to finance. Tailoring strategies to specific local conditions and promoting regional cooperation emerge as crucial factors for driving inclusive and sustainable economic growth in these regions. By incorporating these findings, policymakers can unlock the full potential of industrial development and create pathways to lasting prosperity.